2016
DOI: 10.1111/cod.12559
|View full text |Cite
|
Sign up to set email alerts
|

Level of use and safety of botanical products for itching vulvar dermatoses. Are patch tests useful?

Abstract: The use of natural topical products is widespread among women affected with itching vulvar diseases. Contact dermatitis is a possible adverse effect. Botanical series are of questionable usefulness, owing to the wide variety of botanical ingredients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 28 publications
1
29
0
1
Order By: Relevance
“…There is a myriad of cleansing agents, freshening sprays, and fragranced wipes available commercially marketed for anogenital skin and a perception that ‘natural’ products are safer than synthetic alternatives. A recent study reported that 42/66 (63.6%) patients with chronic vulval itch had applied natural topical products to the vulva . These “natural” products often contain fragrances and preservatives, such as MI and sodium metabisulfite, which we found to be clinically relevant allergens in our patients.…”
Section: Commentmentioning
confidence: 62%
“…There is a myriad of cleansing agents, freshening sprays, and fragranced wipes available commercially marketed for anogenital skin and a perception that ‘natural’ products are safer than synthetic alternatives. A recent study reported that 42/66 (63.6%) patients with chronic vulval itch had applied natural topical products to the vulva . These “natural” products often contain fragrances and preservatives, such as MI and sodium metabisulfite, which we found to be clinically relevant allergens in our patients.…”
Section: Commentmentioning
confidence: 62%
“…34,35 In addition, as described in other study the most popular forms in topical preparations were dermatological cream, ointments and lotions. 36 The highest relative citation frequency (RFC) was attributed to A. vera in the three district Skikda (0.68), Annaba (0.57), and El Tarf (0.43).…”
Section: Discussionmentioning
confidence: 85%
“…In recent years, marine cosmeceuticals compounds exploration in the marine/oceanic habitat has been performed for novel marine cosmeceuticals such as chitosan, marine fish and sponge derived collagens for enhanced cosmeceutical production via biotechnology sch RNA and nanotechnologies production [21,32,33]. Their application in the treatment of skin diseases, diabetes, and arthritis using advanced research on marine or fauna originated cosmeceutical substances evaluated [19][20][21][22]34,35].…”
Section: Cosmeceuticals Sources Formulation Applications and Classimentioning
confidence: 99%
“…It is anticipated that the global cosmeceutical market will hit USD $61 billion by 2020 majorly driven par consumers desired maintain the skin/body care, beauty and resolve the imperfections and anti-ageing [1,29,30,31]. Personal care and beauty industries have the ability to improve Saudi import and export transactions and market (e.g., Banaja Saudi Import Company, Spimaco, Tabuk Pharmaceutical and Biotechnology Manufacturing and Al-Jazeera Pharmaceutical Industries), population income growth, employment and increasing the appetites for quality healthcare and hygiene under the regulation, supervision and coordination Saudi Food and drug Authority (SDFA) and other government stakeholders agencies [6,8,24,25,32,39,40]. The prediction showed that new ingredients will continue to be developed in this sector locally from plant, animal and marine sources [1,2,27,33,41].…”
Section: Benefits Of Local Cosmeceuticals Stakeholders Partnership Anmentioning
confidence: 99%
See 1 more Smart Citation